Aspek Hukum Kontrak Leasing dan Kontrak Financing - Admiral, Admiral (UIR Law Review, 2018)
Leasing Contract and Financing Contract is an Innominaat Contract. Both of this contract have a different goals, characteristic and regulation. Leasing Contract is identical with common Lease Contract, but with an option (Finance Lease) and without an option (Operating Lease),while Financing Contract is a Consumer Finance Contract, where is the debitur is an owner and not a lessee